Investigating the Secondary Electron Emission of Nanomaterials Induced by a High‐Resolution Proton Beam. Issue 4 (13th February 2022) - Cholewa, Marian; Grędysa, Anna; Pozaruk, Andrii; Osipowicz, Thomas; van Kan, Jeroen A.; Dou, Yan X.; Yan, Peiyan; Bettiol, Andrew A.; Maximov, Ivan; Sobanska, Maria; Zytkiewicz, Zbigniew R.; Gogneau, Noelle; et al.
Abstract : Herein, the secondary electron emission (SEE) from 1D nanomaterials in the form of nanorods is investigated. The small beam of a 1.5 MeV + H2 hydrogen with a sub 70 nm in diameter allows studying the SEE with a very high resolution. A wide range of nanomaterials from various laboratories are studied, including thin ZnO and ZnO/GaN nanostructures grown on 1 μm thick Si3 N4 membranes and thick InP, GaN and GaN/AlN nanorod structures grown on bulk Si substrates. By virtue of the small size of the exciting nanobeams, high‐resolution maps could be created presenting an SEE yield from various parts of the structures. This allows us to show that the top parts of nanorods in ZnO, ZnO/GaN, GaN, InP, and GaN/AlN nanostructures emit secondary electrons much more efficiently than the valley areas between nanorods. These results indicate that by a proper design and growth of 1D nanostructures, SEE properties could be improved over those of the traditionally used Au and CsI thin films. This work has been undertaken to find materials with the highest achievable SEE emission, which is a figure of merit for the detection efficiency relevant for the development and application of novel radiation detectors. Abstract : Herein, the secondary electron emission (SEE) from 1D nanomaterials in the form of nanorods is investigated. A wide range of nanomaterials from various laboratories are studied with a high‐resolution proton nanobeam. Results indicate that by proper design and growth of 1D nanostructures, SEE properties could be improved over those of the traditionally used Au and CsI thin films.